2021
DOI: 10.1002/ejsp.2793
|View full text |Cite
|
Sign up to set email alerts
|

Gay = STIs? Exploring gay and lesbian sexual health stereotypes and their implications for prejudice and discrimination

Abstract: Gay men and lesbian women face health inequities as well as disparate treatment from healthcare providers. Stereotypes surrounding sexual health might contribute to these disparities. In five studies (N = 1858), we explored sexual health stereotypes about gay men and lesbian women and their implications in prejudice/discrimination. In Studies 1, 2A and 2B, we found people explicitly associated gay men with promiscuity and sexually transmitted infections (STIs) more than lesbian women or straight men/women. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 87 publications
0
9
0
1
Order By: Relevance
“…This converges with previous research suggesting that individuals who depart from mononormativity may be less socially accepted and therefore at greater risk of stigmatization (Moors et al, 2013) and dehumanization (Rodrigues et al, 2018), even when compared to individuals who depart from heteronormativity. Indeed, even though gay men and same-sex male partners are targets of prejudice and discrimination (Brown & Groscup, 2009;Doan et al, 2015;Rice et al, 2021), acceptance towards sexual minorities has increased in the past few years in some parts of the world (Pew Research Center, 2020). For example, attitudes towards gay and lesbian individuals in Portugal have become more favorable in recent years, particularly after the legalization of same-sex marriage in 2010 (Hagen & Goldmann, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This converges with previous research suggesting that individuals who depart from mononormativity may be less socially accepted and therefore at greater risk of stigmatization (Moors et al, 2013) and dehumanization (Rodrigues et al, 2018), even when compared to individuals who depart from heteronormativity. Indeed, even though gay men and same-sex male partners are targets of prejudice and discrimination (Brown & Groscup, 2009;Doan et al, 2015;Rice et al, 2021), acceptance towards sexual minorities has increased in the past few years in some parts of the world (Pew Research Center, 2020). For example, attitudes towards gay and lesbian individuals in Portugal have become more favorable in recent years, particularly after the legalization of same-sex marriage in 2010 (Hagen & Goldmann, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There is ample research showing that gay men and heterosexual partners have similar relationship functioning (Chonody et al, 2020;Peplau & Fingerhut, 2007;Reczek, 2020;. And yet, gay men (vs. heterosexual individuals) are perceived as more promiscuous, more likely to have risker sexual behaviors and spread STIs (Rice et al, 2021), and less likely to have loving, fulfilling, and serious relationships (Brown & Groscup, 2009;Doan et al, 2015). Much like CNM partners, gay partners are often stigmatized because of their sexual orientation (Lopes et al, 2017;Peplau & Fingerhut, 2007), are targets of violence (Lund et al, 2021), are avoided by others (Buck et al, 2013;Cook & Cottrell, 2021), and are dehumanized (Fasoli et al, 2016).…”
Section: The Experiences Of Cnm Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…All groups were more flexible about boys' gendered behaviour (but not the occupation preferences), while all participants-except for gay participants-supported more traditional gendered behaviour (but not the occupation preferences) for girls. Rice, Hudson, and Noll (2022) examined the nature of sexual healthspecific stereotypes towards gay men and lesbian women as well as the role of these assumptions in prejudice and discrimination. Specifically, through five studies using correlational designs with quantitative and qualitative data (Ntot = 1407), they showed that gay men were more closely associated with risky sexual behaviour and sexual transmitted infections (STIs) than heterosexual men, lesbian women, or heterosexual women, and more closely associated with promiscuity than heterosexual or lesbian women.…”
Section: What We Still Need To Know: the Contributions Of This Specia...mentioning
confidence: 99%
“…Social conditions for men and women who identify as sexual minority have undeniably improved in recent years (Hagen & Goldman, 2020;Twenge et al, 2016), even since Pachankis and Hatzenbuehler's research (2013) on the Best Little Boy in the World Hypothesis (BLBWH). However, negative stereotypes and homonegativity in society have certainly not disappeared (see Rice et al, 2021) and indeed remain substantial in some communities (e.g., fundamentalist religious communities; Bjork- James, 2018;Janssen & Scheepers, 2019;Schwartz & Lindley, 2009). Moreover, those individuals raised before some of these improvements likely experienced substantial stigmatization during formative years, including early adulthood, contributing to negative consequences.…”
Section: Introductionmentioning
confidence: 99%